Penatalaksaan Penyakit Gangren Pulpa di RS Bondowoso, Puskesmas Sumbersari, Wuluhan, Pakusari, dan Mayang Tanggal 18 Juni-29 Juli 2013 - Kiswaluyo Kiswaluyo; Rieza Adhanti; Sisca Hermawati; Chusnul Chotimah; Dika Fitria W (Fakultas Kedokteran Gigi Universitas Jember, 2014)
Drugs and health storage are components of public health services included dental health service in public health center and hospital. Public health center consider root canal treatment and medicament that used for that treatment. The objective of this study was to know treatment of pulp gangrene in four public health centers and a hospital. This study was descriptive observational with cross sectional method. Population of this study was patients who diagnosed pulp gangrene in four public health center and a hospital on Juli to Agustus 2013. This study used probability sampling for taking samples in population continued simple random sampling. The result showed the treatments of pulp gangrene were medication, extraction, and sterilization. Treatment in public health center focused in preventive treatment.